EVALUTION OF LEARNING FACILITIES SUPPORTING CREATIVE PRODUCTS AND ENTREPRENEURSHIP IN MODELING DESIGN AND BUILDING INFORMATION EXPERTISE COMPETENCY - Wisnu Rachmad Pribadi; Ikhwanuddin; Abdul Malik; Rudi Nur Syamsudin; M. Arif Faisal (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
This study aims to gain a general understanding of the state of educational infrastructure and learning facilities for creative and entrepreneurial products, as well as a general understanding of the degree of standard compliance and the appropriateness of the curriculum requirements for Vocational High School Modeling Design and Building Information Expertise Competency. This study employed a descriptive and methodology. An analysis of the infrastructure and learning environments for innovative and entrepreneurial products provides information on the degree of standard compliance. An overview of the condition of learning facilities and infrastructure for creative and entrepreneurial products obtains an illustration that the requirements for facilities and infrastructure for creative and entrepreneurial product learning in DPIB expertise competence are in the form of computer graphics, printers, projectors, computer desks, chairs, and Split AC. Computer graphics have a quantity proportion of 83.3% and a quality proportion of 33.3%, meaning that in terms of quantity it is sufficient but in terms of quality it needs to be improved. This causes the computer's ability to run software or applications, such as SketchUp and AutoCad, to be limited. Computer capabilities in the laboratory 1 & 2 can only install old software or output, such as AutoCad 2016 and SketchUp 2016, and unable installing rendering software. which will affect the level of suitability and the level of adequacy of the needs of the DPIB curriculum where the demand for vocational expertise competencies, especially DPIB expertise competencies which are closely related to graphics to realize superior global competitiveness.